The Usefulness of AI in Academic Research: University Faculty Perceptions and Profiles - Pérez-Penup, Lorena (2025)
Although the use of AI applications in academic research has the potential to significantly boost scientific productivity, successful integration of AI requires a thorough understanding of how this technological wave has impacted university faculty. This study aimed to contribute to that understanding by examining faculty perceptions regarding the usefulness of AI in academic research. The study used a quantitative, exploratory-descriptive methodology with a non-experimental, cross-sectional design. Data was collected through a survey addressing 25 research-related tasks grouped into five categories: Literature Review, Methodology Selection, Reflection on Results, Communicative Activities, and Enhanced Disciplinary Understanding. Responses from 244 faculty members revealed three distinct perspectives: enthusiasts, selective users, and skeptics. The results demonstrate that that AI is perceived as particularly beneficial for activities related to synthesizing information and consolidating knowledge about the discipline. These findings underscore the need for customized AI policies and targeted support to bridge knowledge gaps and promote greater faculty engagement in the use of AI as part of their research activities.